Do organizational characteristics and audit opinion affect zakat performance? - Zakiy, Faris Shalahuddin; Agriyanto, Ratno; Farida, Dessy Noor; Rahmiyanti, Firdha; Fauziah, Najim Nur; Fuadi, Nasrul Fahmi Zaki (Universitas Negeri Surabaya, 2024)
This research aims to examine the influence of organizational characteristics and audit opinion on zakat performance in Indonesia. The study examines 33 zakat institutions in Indonesia from 2017 to 2021, with 151 observations. Zakat performance in this study is measured using activity ratios, growth ratios, and excess zakat scores. The independent variables in this study are organizational characteristics (i.e. organizational age and organizational size) and audit opinion. The data is analyzed using data panel regression. The research findings indicate that audit opinion positively and significantly impacts zakat performance. Organizational size has a positive and significant impact on zakat performance in model 1, while it does not impact other models. Organizational age does not have an impact on zakat performance. This study highlights the importance of effective and efficient zakat management. Additionally, accountability and transparency reflected through audit opinions can minimize the potential for information asymmetry and conflicts of interest between agents and principals. Therefore, the organization's operational experience, asset growth, and audit opinion can enhance zakat performance in terms of the growth of fund collection and the practical and innovative distribution of zakat, infaq, and shadaqa funds.